2023
DOI: 10.1039/d3fo02330c
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting carotenoids as dietary antioxidants for human health and disease prevention

Abstract: Humans are unique indiscriminate carotenoid accumulators, so the human body accumulates a wide range of dietary carotenoids of different types and to varying concentrations. Carotenoids were once recognized as physiological...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 268 publications
0
11
0
Order By: Relevance
“…Carotenoids are natural fat-soluble pigments found in plants, and their provitamin A and antioxidant activities benefit human health [ 86 ]. Thiamine and riboflavin are engaged in a variety of crucial metabolic pathways in the body [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carotenoids are natural fat-soluble pigments found in plants, and their provitamin A and antioxidant activities benefit human health [ 86 ]. Thiamine and riboflavin are engaged in a variety of crucial metabolic pathways in the body [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cocoa powder, chocolate, wine and tea (especially green tea) are high in total flavonoids ( 23 25 ). Both carotenoids and flavonoids are reported to reduce the risk of non-communicable disease, notably CVD and type 2 diabetes ( 26 30 ). Both clinical and observational studies have also pointed to beneficial effects of consuming whole berries, juices, and anthocyanin extracts on reducing diabetes and CVD risks ( 31 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gavage dose of LUT was set at 100 mg per kg (BW per day), 16 the gavage dose of EGCG was set at 500 mg per kg (BW per day), and the ratio between LUT and EGCG was referred from the previous study. 18 LUT was dissolved in soybean oil, and EGCG was dissolved in water to prepare the corresponding concentration solution.…”
Section: Methodsmentioning
confidence: 99%
“…14 Dietary supplementation of LUT can prevent or delay the development of ocular inflammatory diseases such as AMD and RP, by protecting the retina from ischemia/hypoxia damage through antioxidant, antiinflammatory and blue light absorption properties. 15,16 Recently, Zhang et al have found that an LUT dose of 200 mg kg −1 promoted the survival of photoreceptors in mice, and increased the expression of rhodopsin in rod cells and the expression of opsin in cone cells. Further research found that LUT delayed photoreceptors by exerting anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%